Singular value analyses of voltage stability on power system considering wind generation variability - Pina, Aline Petean [UNESP] (2014)
Transmission Systems worldwide, that were designed and built to operate with predominantly conventional synchronous generation, are advancing to integrate large amounts of renewable energy generators. These renewable generators are sited at resource-rich locations, causing a geographical shift in power injections into transmission systems, subjecting them to undue stress and making them operate in new states. In many transmission systems, capacities to integrate wind resource are exhausted or are being upgraded to accommodate higher wind generation penetration. Examples may be seen in Germany, Ontario (Canada) and Texas. In these situations, where transmission system capacities have been reached, it is important to assess voltage stability by considering (a) wind generation and (b) possible effect of uncertainty in forecast. In this work, a systematic approach of studying voltage stability is proposed. Using an optimal power flow algorithm, the Hessianmatrix of power balance equations is determined that relates changes in minimum singular values of system Jacobian to changes in bus-wise real power injections. This relationship is used to examine effect of uncertainty of wind power forecast on voltage stability. The proposed method is used to study the effects of uncertainty on system voltage stability of 6-bus, 57-bus and 118-bus IEEE and 45-bus South Brazilian test systems, for the real analyses is used 600-bus and results are reported. Considering the simplification of computation, the proposed method has a clear advantage compared to the conventional Jacobian technique using repeated OPF solutions